Clinical and electroencephalographic correlations in patients with cerebral ischemic hemispheric stroke in early recovery period of disease - S. O. Medvedkova (Zaporozhye State Medical University, 2018)
The aim is to investigate the state of bioelectric activity of the brain in comparison with clinical neurological data in patients with cerebral ischemic hemispheric stroke (CIHS) in the early recovery period of the disease. Materials and methods: complex clinical and instrumental research was done in 60 patients (23 men and 37 women, age 58 (54; 66) years) with cerebral ischemic hemispheric stroke in early recovery period of disease, which included the indication according to the stroke scale of National Institute of Health (NIHSS) and modified Rankin Scale on the 10th, 30th, 90th and 180th day of disease. To evaluate the functional state of the brain on the 10th day of CIHS, computer electroencephalography was performed with the determination of the parameters as for spectral analysis of the bioelectric activity of the brain. Results. It was defined that with the level of disability on the 180 day of CIHS most closely related to each other the value of the relative spectral power (RSP) rhythms δ-subrange of affected hemisphere (AH) (R = +0.41, P < 0.05), RSP rhythms δ-subrange of intact hemisphere (IH) (R = + 0.43, P < 0.05), RSP rhythms θ1-subrange of AH (R = + 0.42, P < 0.05), RSP rhythms θ1-subrange of IH (R = +0.46, P < 0.05), RSP rhythms θ2subrange of AH (R = +0.38, P < 0.05), RSP rhythms θ2-subrange of IH (R = +0.42, P < 0.05), RSP rhythms θ-subrange of AH (R = +0.41, P < 0.05), RSP rhythms θ-subrange of IH (R = +0.43, P < 0.05), and also integral coefficients DAR AH (R = +0.41, P < 0.05), DAR IH (R = +0.45, P < 0.05), DTABR AH (R = +0.52, P < 0.05), DTABR IH (R = + 0.51, P < 0.05), TAR AH (R = +0.41, P < 0.05) and TAR IH (R = +0.41, P < 0.05). Conclusion. The level of disability on the 180th day of CIHS is correlated with the values of DTABR of the affected (R = +0.52, P < 0.05) and intact hemisphere (R = + 0.51, P < 0.05) on the 10th day of the disease.